2020
DOI: 10.1371/journal.pone.0233092
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of routine health information and associated factors among health workers in Hadiya Zone, Southern Ethiopia

Abstract: Background The utilization of routine health information is an essential factor of the structural capacity of health departments and public health performance depends on the effectiveness of information use for routine and programed decisions. Considerable research has been conducted in health data collection and ways to improve data quality, but little is known about utilization of routine health information among health workers in Ethiopia in general and in the study area in particular. Objectives The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
37
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 11 publications
21
37
7
Order By: Relevance
“…PMT members competent in DHIS2 data tasks were 2.41 times more likely to have a higher level of commitment to use DHIS2 data for decision making than those incompetent in DHIS2 data tasks (AOR 2.41, 95% CI 1.27-4.55). This finding was in line with those reported in studies conducted in Ethiopia [ 25 ], Ghana [ 2 ], Nairobi, Kenya [ 26 ], and another study conducted at the health facilities in Kenya ( P =.03) (AOR 4.32, 95% CI 2.34-7.98) [ 27 ]. However, this finding was inconsistent with that of a study conducted in Kenya, which indicated that competency in DHIS2 task has no association with the performance of the health information systems [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…PMT members competent in DHIS2 data tasks were 2.41 times more likely to have a higher level of commitment to use DHIS2 data for decision making than those incompetent in DHIS2 data tasks (AOR 2.41, 95% CI 1.27-4.55). This finding was in line with those reported in studies conducted in Ethiopia [ 25 ], Ghana [ 2 ], Nairobi, Kenya [ 26 ], and another study conducted at the health facilities in Kenya ( P =.03) (AOR 4.32, 95% CI 2.34-7.98) [ 27 ]. However, this finding was inconsistent with that of a study conducted in Kenya, which indicated that competency in DHIS2 task has no association with the performance of the health information systems [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…times more likely to have high commitment when compared to those who has low motivation to use DHIS2 data for their decision making[AOR = 1.80, 95% CI: (1.00, 3.25)]. This study (P-value = .033) was in line with study done in Ethiopia (24) and Ghana (P-value = .014) (2).…”
Section: Discussionsupporting
confidence: 82%
“…The odds of respondents with regular supportive supervision visits were 2.84 times more likely to have a high level of commitment among PMT members than those who did not have regular supportive supervision[AOR = 2.84, 95 CI:( 1.50, 5.37)]. The result was similar to study conducted in Ethiopia (24,28) and Ghana that shows commitment to use DHIS2 data was directly associated with the day to day managerial supervision one has (P-value = .045) (2).…”
Section: Discussionsupporting
confidence: 77%
“…Generally, in Sub-Saharan Africa, the level of health information utilisation at primary health care, and the district is poor [23]. In Ethiopia, the level of HMIS data utilisation for different decision-making purposes has been reported at 57.9%-62.7% [28][29][30]. In a recent study in Zanzibar, it was reported that only 42% of the healthcare workers used HIMS data for monitoring and evaluation, 35% for planning, 23% for supply and drugs management, 18% for budgeting, and 10% for disease outbreak preparedness [31].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study in Zanzibar, it was reported that only 42% of the healthcare workers used HIMS data for monitoring and evaluation, 35% for planning, 23% for supply and drugs management, 18% for budgeting, and 10% for disease outbreak preparedness [31]. Factors associated with good utilization of HMIS data have been described to include staff motivation, training, supportive supervision, a good perceived culture of health information, competence, and decisions based on superior directives [29][30].…”
Section: Discussionmentioning
confidence: 99%